A Study to Assess the Effectiveness of Foot Reflexology for Prevention of Breast Engorgement among Lower Segment Cesarean Section Mothers in a Selected Hospital of a Metropolitan City - Loladiya, Nilofar; Lobo, Jacintha (International Journal of Nursing Research, 2023)
Background: Puerperium is the period beginning immediately after the birth of the child and it is an important moment in the life of a woman. Breast engorgement is very common and has an effect on self and newborn care. Breast engorgement is distention or vascular congestion in the process of swelling of the breast tissue brought about by an increase in blood and lymph supply to the breast as the body produces milk, which precedes true lactation. Reflexology has huge health benefits and it alleviates women’s pregnancy and nursing experiences too. Reflexology increases the health and well-being of women and provides a comforting and nurturing environment for both mother and baby. Lower segment cesarean section (LSCS) being an operative procedure restricts the movement of mother which hinders self and newborn care. Reflexology aims to engage body’s own healing process, treating the person as a whole, i.e. the mind, body, and soul. Aim: This study aims to assess the effectiveness of foot reflexology for the prevention of breast engorgement among LSCS. Materials and Methods: A quasiexperimental design was used for this study. The study was performed on 80 postnatal mothers of postnatal ward of a selected hospital of a metropolitan city. Results: The study results show that there was a reduction in breast engorgement among LSCS mothers after the application of foot reflexology which was statistically verified. Conclusion: The analysis of data showed that foot reflexology can be used for the prevention of breast engorgement among LSCS mothers.